Design and Implementation of Flexible Employment System Based on Uniapp - Xiong, Fangge; Nan, Chuxi (International Journal of Computer Science and Information Technology, 2024)
To help people achieve and do flexible employment, a system has been developed to provide and publish job and job search information and supervise the entire work process. The back end of the system uses the Springboot framework, the front end uses the Vue framework, and the MySQL database to develop a flexible employment system. The front-end of the system is the client; its main functions include publishing and searching job and job searching information, generating and evaluating orders, etc. The main function of the backend is to manage the data generated by the front end, such as managing user account information, user personal information, order information, etc. Flexible employment systems can allow users to achieve flexible job positions conveniently, improve the stability of flexible employment, and reduce social unemployment rates.